A Study on Poles and Zeros and Meromorphic Functions with Non-Zero Derivatives and Related Polynomial Differentials: Exploring Uniqueness Theorems and Growth Limitation of Meromorphic Functions with Polynomial Differentials (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In the study, we concentrated on the Uniqueness Theorems and Meromorphic Structure Deficiencies, Growth limitation regarding poles and zeros and meromorphic functions with non-zero subordinates and related polynomial differentials and Fix points normal and characteristic groups of some homogeneous polynomials. Additionally we study Angular conveyance of meromorphic functions concerning homogeneous and differential polynomials.